Sibling risk of hospitalization for heart failure – A nationwide study. (15th November 2016) - Lindgren, Magnus P.; Smith, J. Gustav; Li, Xinjun; Sundquist, Jan; Sundquist, Kristina; Zöller, Bengt
Abstract: Background: The familial risks of heart failure (HF) remain largely undetermined. This nationwide follow-up study aimed at determining risk of hospitalization for HF conferred by affected siblings. Methods and results: Swedish Multi-generation Register data, with records of at least one full sibling available at start of follow-up, were linked to the Hospital Discharge Register data for 1987–2010. The oldest participants were aged 78 years in 2010. Relative risks, standardized incidence ratios (SIRs), of HF hospitalization were calculated for individuals with siblings hospitalized with HF compared with those whose siblings were not. Adjustments were made for common HF comorbidities, age, time period, socioeconomic status and region. During the 24 year follow-up (1987–2010) 23, 212 individuals (7155 females), were hospitalized because of HF. From this total, 1121 had at least one full sibling hospitalized for HF. Sibling risks were generally similar for males and females. The SIR of HF hospitalization was 1.62 (95% confidence interval 1.54–1.70) for individuals with one affected sibling and 15.46 (12.82–18.50) for individuals with two affected siblings. The SIR conferred by one or more affected siblings was 2.67 (2.24–3.16) below the age of 50 years, 1.92 (1.75–2.10) between 50 and 59 years of age, 1.63 (1.52–1.76) between 60 and 69 years of age, and 1.54 (1.38–1.71) between 70 and 78 years of age. Spouses had low familial risks: SIR = 1.04 (1.03–1.06). Conclusions: Familial factors are important risk factors in HF, with particularly high risks among individuals with two or more affected siblings and in early onset of HF.